THE THEOLOGICAL DISCUSSION OF THE KHARIJITES (KHAWARIJ) ON THE ISSUES OF TAKFIR (ACCUSING OF UNBELIEF), AND THE STATUS OF MUSLIMS AND POLYTHEISTS - Abd Rahman, Saodah Binti (Al-Shajarah Journal of the International Institute of Islamic Thought and Civilization (ISTAC), 2014)
THE THEOLOGICAL DISCUSSION OF THE KHARIJITES (KHAWARIJ) ON THE ISSUES OF TAKFIR (ACCUSING OF UNBELIEF), AND THE STATUS OF MUSLIMS AND POLYTHEISTS